Keats’s Reading / Reading Keats
XXVI, 362 p. 13 illus.
Keywords: This book explores John Keats’s reading practices and intertextual dialogues with other writers. It also examines later writers’ engagements with Keats’s poetry. Finally, the book honors the distinguished Keats scholar Jack Stillinger and includes an essay surveying his career as well as a bibliography of his major publications. The first section of the volume, “Theorizing Keats’s Reading,” contains four essays that identify major patterns in the poet’s reading habits and responses to other works. The next section, “Keats’s Reading,” consists of six essays that examine Keats’s work in relation to specific earlier authors and texts. The four essays in the third section, “Reading Keats,” consider how Keats’s poetry influenced the work of later writers and became embedded in British and American literary traditions. The final section of the book, “Contemporary Poetic Responses,” features three scholar-poets who, in poetry and/or prose commentary, discuss and exemplify Keats’s impact on their work.